FLOW-3D software for substantiation the layout of the port water area. Issue 1 (July 2020) - Pan, B; Belyaev, N
Abstract: It is necessary to exclude the occurrence of significant waves in the inner water area of the port and at the berthing facilities when designing breakwaters. The article presents the results of the calculations of water movement in the harbor area. The most secure options for the location of the port entrance and its size for a given object were identified. The possibility of using the FLOW – 3D program to select planned and constructive solutions at the stage of the preliminary layout of the port water area is substantiated.